Flai (fludarabine, cytarabine, idarubicin) plus low‐dose Gemtuzumab Ozogamicin as induction therapy in CD33‐positive AML: Final results and long term outcome of a phase II multicenter clinical trial. Issue 5 (2nd March 2018) - Candoni, Anna; Papayannidis, Cristina; Martinelli, Giovanni; Simeone, Erica; Gottardi, Michele; Iacobucci, Ilaria; Gherlinzoni, Filippo; Visani, Giuseppe; Baccarani, Michele; Fanin, Renato
Abstract: The aim of this prospective clinical trial was to evaluate the efficacy and safety of a combination of Gemtuzumab‐Ozogamicin (GO) and FLAI scheme (fludarabine, cytarabine, idarubicin) as a first‐line therapy in CD33 positive AML. We treated 130 patients, aged <65, with a median age of 52 years. FLAI‐GO induction regimen included fludarabine (30 mg/sqm) and cytarabine (2 g/sqm) on days 1–5; idarubicin (10 mg/sqm) on days 1, 3, and 5; and GO (3 mg/sqm) on day 6. SCT was planned for all high‐risk AML patients, after consolidation with intermediate doses of cytarabine and idarubicin and a high dose of cytarabine. CD33 expression exceeded 20% in all cases. Primary endpoints of the study included feasibility, overall response rate (ORR) and toxicity. Secondary endpoints included the evaluation of MRD by WT1 expression, feasibility and outcome of consolidation with SCT, overall survival (OS) and disease‐free survival (DFS). After induction with FLAI‐GO, complete remission (CR) rate was 82%. Four patients achieved partial remission (PR) and 12% were resistant (ORR 85%); death during induction (DDI) was 3%. The hematological and extra hematological toxicity of FLAI‐GO was manageable; 45% of patients experienced transient and reversible GO infusion related adverse events. In the setting of patients who achieved a cytological CR after FLAI‐GO, the mean of WT1 copies dropped from 8337±9936 copies/10 4 ABL (diagnosis) to 182 ± 436 copies after induction therapy ( p  = 0.0001) showing a very good disease debulking. After a median follow‐up of 54 months, 67/130 (52%) patients were alive. The probability of 1, 2, and 5‐year OS was 80%, 63%, and 52%, respectively. The probability of 1, 2, and 5‐year DFS was 77%, 58%, and 52%, respectively. Allogeneic and autologous SCT was performed in 60 (46%) and 23 (18%) patients, respectively. In summary, the final results of this trial confirm that FLAI‐GO is an active and safe treatment strategy for CD33‐positive AML patients aged ≤ 65 years, allowing a high ORR, a good disease debulking, favorable safety profile, low DDI, and subsequent high SCT rate. The encouraging results of this trial, consolidated by a long follow‐up, support the reintroduction of GO in clinical practice.